PREVENTION EFFORTS OF CHILDREN AS ACTORS IN PERSPECTIVE CRIME OF NARCOTICS VALUE OF JUSTICE - Frans Simangunsong; Teguh Prasetyo; Sri Endah Wahyuningsih (Surakarta Law and Society Journal, 2018)
Drugs are a serious problem for this nation. These illicit goods undermine anyone. People'srepresentatives, judges, artists, pilots, students, workers, even housewives do not escape drug trafficking. In terms of age, drugs also never choose their victims, ranging from children, teenagers, adults, even to the elderly. Indonesia is a 'paradise' of drug trafficking. Why not, if judging from the circulation of drugs in the world, our country ranks third as the largest drug market in the world.Crime prevention can be done either by using criminal justice (other judicial) or other means outside criminal justice (non-judicial). Efforts to transfer the process from the judicial process to the nonjudicial process in the handling of narcotics abuse by children, are basically an effort to solve narcotics abuse committed by children outside the criminal justice channel. That is, the transfer of the process from the judicial process to the non-judicial process in the handling of narcotics abuse by children, is basically an effort to avoid children from the application of criminal law and punishment. Legal treatment for minors in the case of narcotics trafficking should receive serious attention. Law enforcers and process and decide must be sure that the decisions taken will be a strong basis for returning and regulating children towards a good future to develop themselves as citizens who are responsible for the life of the nation. Keywords: Prevention, Children, Crime, Narcotics, Value of Justice